Ibrah kemunduran Bani Abbasiah pada generasi mendatang - Assalim, Fasthothi Kahfi (Maliki Interdisciplinary Journal, 2024)
The third Islamic caliphate that ruled between 750 and 1258 AD was the Abbasids. There were several factors that influenced the decline of the Abbasid Dynasty, namely internal factors and external factors. With the existence of these factors of decline, lessons can be taken as they should. The next generation is the successor of the nation, the stronger the successor of the nation the stronger the state. This study explains the brief history of the Abbasid Dynasty, the factors of the decline of the Abbasid dynasty and the wisdom of the Abbasid Dynasty’s decline. The results of this study show that it is very important to take lessons from the decline of the Abbasids. This can be done by strengthening unity, increasing professionalism in the caliphate and increasing sociality towards others.